Storytelling in Organizations A Narrative Approach to Change, Brand, Project and Knowledge Management - Thier, Karin (Management for Professionals,, 2018)
This book highlights storytelling as a concrete and viable method which can be used in various operational fields in organizations: from change management to project management and knowledge management, it presents employees' stories on past projects and the diverse, essential aspects of corporate culture they reveal, in an easy-to-comprehend and entertaining fashion. These stories focus on specific but generic experiences which can be adapted and exploited by the reader to ultimately tap into hidden knowledge and increase transparency during daily routines in his or her own organization. Knowledge managers, coaches, and strategists alike will find a 'real-life' connection through these stories, helping them improve their own storytelling methods. The book also provides exhaustive information on the latest storytelling methods and strategies. The adaptations Thier has made to bring learning histories to corporate settings accelerates the capture, flow, and application of organizational knowledge that speeds up changes to improve operations! George Roth (Principal Research Associate at MIT Sloan School of Management, Boston, United States).